Moral Message on Movie [John Fiske Semiotics Analysis]: Pesan Moral Pada Film [Analisis Semiotika John Fiske] - Sari, Dessy Nanda; Febriana, Poppy (Indonesian Journal of Innovation Studies, 2023)
The purpose of this study is to find out the moral message contained in the film The New Rich People. With descriptive qualitative research methods, using John Fiske semiotics analysis though three levels, namely: Reality Level, Representation Level, and Ideology Level. The results of this study show that the film The New Rich People there are many moral message conveyed to the audience, harmonious, have children who are smart and good, love each other and care for each other, friends who are always there in a state of joy and sorrow. A simple life is better than a luxurious life but not feeling happy, not making out something can be bought with money.